A hard straight - Toshima, Goro; Sablosky, Lindsay; Independent Television Service; One Arm Productions; New Day Films ([S.l.] : One Arm Productions ; [Harriman, N.Y.] : New Day Films, 2004)
Shot on location in Los Angeles and San Francisco over a period of two years, producer Goro Toshima documents the successes and failures of three prison parolees
Camera, Goro Toshima ; editor, Kim Roberts
Regina Allen, Richard "Smiley" Martinez, Aaron Shephard
DVD
no Master.
Keywords: Allen, Regina; Martinez, Richard; Shepard, Aaron; Parole -- California -- Case studies